An Oral Microbiome Perspective: Postbiotics as a Prospective Therapeutic Agents in Dental Medicine (A Short Communication) - Friyandika, Aditya Rediana; Afan, Luthfian Ibnu (Formosa Journal of Sustainable Research, 2024)
Recently, there has been an increase in interest in the use of microorganisms that are used as a preventive effort to prevent dental and oral health problems, known as probiotics, prebiotics, synbiotics, and postbiotics. As more and more clinical trials of the use of microorganisms show positive results for certain conditions, Postbiotics have several advantages, including safety, longer shelf life, absence of risk and patentability, which makes them more attractive than probiotics. This review covers a wide range of aspects, starting with an introduction, terminology, role of post biotik, and a brief mechanism of action. The discovery section concludes by highlighting the challenges and future directions to improve postbiotic discovery. The review concludes by highlighting the ongoing applications of postbiotics in expanded clinical trials, providing a comprehensive overview of the current landscape in postbiotic development